Capabilities of hepatitis B surface antigen are divergent from hepatitis B virus DNA in delimiting natural history phases of chronic hepatitis B virus infection - Zhang, Zhanqing; Lu, Wei; Huang, Dan; Zhou, Xinlan; Ding, Rongrong; Li, Xiufen; Wang, Yanbing; Lin, Weijia; Zeng, Dong; Feng, Yanling (Frontiers in Immunology, 2022)
Objective: Quantitative HBsAg and HBV DNA in the natural history of chronic HBV infection have not been rationally evaluated. This study aimed to re-characterize quantitative HBsAg and HBV DNA in the natural history phases. Methods: 595 and 651 HBeAg-positive patients, and 485 and 705 HBeAg-negative patients, were assigned to the early and the late cohorts, respectively. Based on the ‘S-shape’ receiver operating characteristic (ROC) curves, the HBeAg-positive sub-cohorts with possibly high HBV replication (PHVR) and possibly low HBV replication (PLVR), and the HBeAg-negative sub-cohorts with possibly high HBsAg expression (PHSE) and possibly low HBsAg expression (PLSE), were designated, respectively. Results: The areas under ROC curves (AUCs) of HBsAg and HBV DNA in predicting HBeAg-positive significant hepatitis activity (SHA) in the early cohort, sub-cohort with PHVR and PLVR were 0.655 and 0.541, 0.720 and 0.606 and 0.553 and 0.725, respectively; in the late cohort, sub-cohort with PHVR and PLVR were 0.646 and 0.501, 0.798 and 0.622 and 0.603 and 0.674, respectively. The AUCs of HBsAg and HBV DNA in predicting HBeAg-negative SHA in the early cohort, sub-cohort with PHSE and PLSE were 0.508 and 0.745, 0.573 and 0.780 and 0.577 and 0.729, respectively; in the late cohort, sub-cohort with PHSE and PLSE were 0.503 and 0.761, 0.560 and 0.814 and 0.544 and 0.722, respectively. The sensitivity and specificity of HBsAg ≤4.602 log10 IU/mL in predicting HBeAg-positive SHA in the early cohort were 82.6% and 45.8%, respectively; in the late cohort were 87.0% and 44.1%, respectively. The sensitivity and specificity of HBV DNA >3.301 log10 IU/mL in predicting HBeAg-negative SHA in the early cohort were 73.4% and 60.8%, respectively; in the late cohort were 73.6 and 64.1%, respectively. Conclusion: Quantitative HBsAg and HBV DNA are valuable but their capabilities are divergent in delimiting the natural history phases.